Impact of home-based aerobic training combined with food orientation on food consumption, daily physical activity and cardiorespiratory fitness among breast cancer survivors: six-month clinical trial - Reis, Andréa Dias; Lima, Luciana Sato de; Barros, Êmili Amice da Costa; Bertoli, Josefina; Gobbo, Luís Alberto; Silva, Camila Buonani da; Garcia, João Batista Santos; Freitas Júnior, Ismael Forte (São Paulo Medical Journal, 2021)
BACKGROUND: Anticancer treatment gives rise to adverse effects such as increased pain and changes to body weight and menstrual cycles, with negative effects on activities of daily living. OBJECTIVE: To analyze the effect of food orientation combined with supervised (face-to-face, FF) versus home-based (HB) aerobic training on lifestyle (food consumption and daily physical activity (PA) levels), body composition, metabolic profile and cardiorespiratory fitness, among breast cancer survivors. DESIGN AND SETTING: Clinical trial study (six months) conducted at a public university in Presidente Prudente, Brazil. METHODS: Twenty-three female breast cancer survivors (40-75 years old) were allocated to aerobic training groups, either FF or HB. Both groups were trained and received food orientation. They were evaluated through a dietary record, ergometric treadmill test and blood test and the Baecke questionnaire. RESULTS: After six months, both groups had reduced their lipid levels, total energy consumption and polyunsaturated fat intake, and had increased their PA levels and treadmill test durations. However, only the HB showed reduced carbohydrate percentage and increased folic acid; and only the FF showed reduced lipid, saturated fat and sodium levels, along with increased carbohydrate and protein levels. No differences in body composition or metabolic profile were found. CONCLUSIONS: These results demonstrated the feasibility of HB aerobic training. In isolation, HB showed greater regulation of carbohydrate percentage and increased folic acid levels. Moreover, these breast cancer survivors presented improvements in food consumption, PA levels and cardiorespiratory fitness, while also maintaining their body composition and metabolic profile after the intervention, independent of the group. CLINICAL TRIAL REGISTRATION: NCT03494400.